Ioxynil and diethylstilbestrol disrupt vascular and heart development in zebrafish - Li, Yi-Feng (2020)
Endocrine disruption is one of the consequences of industrialization and chemicals released into the environment have a profound impact on organisms. Waterborne micromolar concentrations of ioxynil (IOX) and diethylstilbestrol (DES) in fish affect the development of the heart, vasculature and thyroid gland.